Perceived Organization Support and Work Engagement toward Employee Performance with Motivation as Mediating Variable - Suwarno, Suwarno; Kesuma, Indrawati Mara; Aprianto, Ronal; Anggraini, Susia; Nuraini, Betti; Paleni, Herman; Surajiyo, Surajiyo (PT. Riset Press International, 2023)
PT. Pos Indonesia is a company that is State-Owned Enterprise (BUMN) engaged in courier services, logistics and financial services throughout Indonesia. This study aims to determine the perception of organizational support and work involvement on performance with motivation as a mediating variable. The research method used is quantitative and the sample in this study is 33 employees at PT. Pos Indonesia Lubuklinggau and collected 33 respondent questionnaires. The data analysis technique uses SEM Partial least squares with the help of the smart PLS 3.2.9 application to collect data using a questionnaire. The results of this study indicate 1. Perceived organization support has a positive but not significant effect on motivation 2. Work engagement has a positive and significant effect on motivation 3. Perceived organization support has a positive and significant effect on performance 4. Work engagement has a positive and significant effect on motivation 5 Motivation has a positive and significant effect on motivation significant to performance 6. Motivation cannot mediate perceived organizational support on performance 7. Motivation has been shown to mediate work engagement on performance.